Food52 any night grilling : 60 ways to fire up dinner (and more) - Disbrowe, Paula (Ten Speed Press, 2018)
A collection of recipes from the creators of the Food52 culinary website features such dishes as shrimp tacos, green chile cheeseburgers, and skirt steak with salsa verde, along with time-saving tips and flavor-enhancing techniques.